Kajian konsep Dan Reka Bentuk Pembungkusan Produk Berasaskan Ikan: Keropok Lekor - Seri Adina, Zainal Abidin (Universiti Malaysia Sarawak (UNIMAS), 2006)
Keropok Lekor is a traditional cuisine from the East Peninsular states specifically Terengganu. It has a high potential and marketable for local and international level. The main constrain in marketing this product globally are the conceptual designs of packaging and poor distributional strategies. This study determine Keropok Lekor's conceptual designs and strategies of marketing. The main strategy is to disperse into local market before penetrating into the global market using modern designing concepts. Effective strategic and conceptual design will open a wild wide market for our local traditional food to reach international level